A Comparison of the Effect of Text-Picture and Audio-Picture Annotations in Second Language Vocabulary Recall among Iranian EFL Learners (GIST – Education and Learning Research Journal, 2016)
The present study compared the effect of text-picture and audio-picture multimedia annotations in second language vocabulary recall among Iranian EFL learners. The participants were selected from two classes of 80 students who were studying advanced-level English at in a language institute in Iran. Their level of English proficiency was determined on the basis of their scores on the PET proficiency test. Sixty-two students were selected for the main procedure, and were then randomly divided into two experimental groups: the textannotation and audio-annotation group; and a control group. After answering a vocabulary pretest, participants clicked on the highlighted unknown words to access available annotations while reading. The text-picture group was able to see textual explanation and pictorial description, and the audio-picture group was able to see pictorial description explanation and hear a spoken explanation. After reading, students completed the post-tests. The results of the study demonstrate that audio-picture annotation is more effective than text-picture annotation in facilitating immediate L2 vocabulary recall. The results suggestthat providing audio or text annotation of new words can help recall of new vocabulary when reading.
Keywords: Text annotation; audio annotation; multi-media annotation; vocabulary